What Drives Bank Margins During and Post-Crisis? A Comparison between Islamic and Conventional Banks - Nurhafiza Abdul Kader Malim; Tajul Ariffin Masron (Asian Academy of Management Journal of Accounting and Finance, 2018)
This paper examines the margins of Islamic and conventional banks particularly in countries where Islamic banking is systemically important using the Generalized Method of Moments (GMM) estimator technique. In evaluating the impact of the global financial crisis, we separately consider the entire period (2006–2013), during crisis period (2007– 2009) and post-crisis period (2010–2013) to gain new insights on the determinants of margins in a dual banking system. The findings indicate that the determinants differ across Islamic and conventional banks during crisis and post-crisis periods. We uncovered evidence suggesting that size, regulatory quality, inflation and overhead costs are important determinants of margins of Islamic banks. The results suggest the significant effects of market concentration, credit risk and overhead costs on conventional banks’ margins. Interestingly, the results reveal different impacts of the crisis on both types of banking system.